Implementing the science, technology, and innovation policy of the Federal Republic of Germany and its implications for Vietnam - Nguyen Thi Hoa Mai (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2025)
An outline of Germany’s science, technology, and innovation policy’s execution is provided in this article, along with information about the country’s accomplishments and shortcomings. It then goes on to discuss the ramifications for Vietnam. Code: 24101503